The Effectiveness of Geng Asbul Media to Improve Expressive Language Skills of Early Childhood - Kurniasih; Yudha, Rivo Panji (Kirana Publisher (KNPub), 2024)
This study aims to determine the effectiveness of Geng Asbul media to improve expressive language skills of early childhood. The research method used is pre-experiment with one group pretest posttest design. The research subjects were class B students at Pos PAUD Pelangi, totalling 16 people, with the sampling technique using purposive sampling. The results showed that there was a significant increase in children's expressive language ability after being treated with Geng Asbul. The average value of children's expressive language ability in the pretest was 26,5, while in the posttest it increased to 37,56. Hypothesis testing shows that the significance value (2-tailed) is 0.000 <0.05, so the null hypothesis is rejected and the alternative hypothesis is accepted. Thus, it can be concluded that there is a significant difference between the pretest and posttest values of language skills of early childhood.